Comparison of Symmetry of Plantar Pressure Distribution in Adolescent’s Female with Selected Knee Abnormalities during Walking on Slope - Zehtab Asghari, Haniyeh; Jafarnezhadgero, Amir Ali; Azarbaijany, Mohammad Ali (Journal of Clinical Physiotherapy Research, 2022)
Introduction: The plantar pressure acts between the foot and the support surface during everyday locomotor activity. Information derived from plantar pressure distribution symmetry is to be important in gait and posture researches for diagnosing lower limb problems, footwear design, injury prevention, and other applications. Hence, this paper aimed to evaluate plantar pressure distribution symmetry in adolescent girls with genu varum, genu valgum, and healthy knees. Materials and Methods: In this quasi-experimental study, 45 adolescent females with genu valgum (n=15), genu varum (n=15), and healthy knees (n=15) in the age ranging from 14 to 17 years, who were selected after an invitation and diagnosis by an orthopedic doctor or a specialist, participated. The plantar pressure values were examined in 10 anatomical areas of plantar pressure on 0, and ±10% slopes in the stance phase of gait. Two-way analysis of variance with repeated measures was used for statistical analysis in significance level of 0.05. Results: No significant differences were observed in the symmetry variables of plantar pressure distribution among the groups. The maximum plantar pressure on the 1thmetatarsus had better symmetry in the slope of 10% for genu varum, -10% for genu valgum, and level zero for the healthy group. Conclusion: The results showed that genu varum and genu valgum abnormalities affect the symmetry indices of plantar pressure distribution in adolescent girls; Also, people with knee deformity had better symmetry at a ±10% slope, which can suggest correcting the deformation of adolescent girls. Therefore, the slope ±10% can suggest improving the plantar pressure distribution pattern in adolescent girls with genu varum and genu valgum knees.